2011
DOI: 10.1038/ismej.2011.100
|View full text |Cite
|
Sign up to set email alerts
|

Huanglongbing alters the structure and functional diversity of microbial communities associated with citrus rhizosphere

Abstract: The diversity and stability of bacterial communities present in the rhizosphere heavily influence soil and plant quality and ecosystem sustainability. The goal of this study is to understand how ‘Candidatus Liberibacter asiaticus’ (known to cause Huanglongbing, HLB) influences the structure and functional potential of microbial communities associated with the citrus rhizosphere. Clone library sequencing and taxon/group-specific quantitative real-time PCR results showed that ‘Ca. L. asiaticus’ infection restruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
124
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(149 citation statements)
references
References 79 publications
20
124
0
5
Order By: Relevance
“…A growing number of studies have focused on understanding how the plant microbiome changes during disease development (15,17,(20)(21)(22)(23)(24)(25)(26). While results from these studies suggest that plant-associated microbial communities undergo perturbation during environmental change or disease progression, one may alternatively argue that the disease itself is a consequence of complex changes to the communities.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…A growing number of studies have focused on understanding how the plant microbiome changes during disease development (15,17,(20)(21)(22)(23)(24)(25)(26). While results from these studies suggest that plant-associated microbial communities undergo perturbation during environmental change or disease progression, one may alternatively argue that the disease itself is a consequence of complex changes to the communities.…”
mentioning
confidence: 88%
“…As for root microbiota, the declining health state of the trees may have altered the composition and amounts of root exudates produced. Trivedi et al (24) reported HLB infection significantly alters the abundances of functional genes in the citrus rhizosphere that are involved in carbon fixation, nitrogen cycling, phosphorus utilization, and metal homeostasis, which reflected a state of environmental change. On the other hand, since the relative abundance of Liberibacter spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative PCR (qPCR) qPCR was performed to determine gene copy numbers for bacteria and fungi, including α-Proteobacteria, β-Proteobacteria, Fimiricutes, Actinobacteria, Acidobacteria and Basidiomycota, using the primers and conditions described previously by Trivedi et al (2012). Spearman correlation analyses were performed by using the XLSTAT software (Addinsoft SARL, Paris, France) to test the relationship between relative abundance determined by qPCR and the relative abundance determined by pyrosequencing.…”
Section: Molecular Analysismentioning
confidence: 99%
“…HLB not only affects plant health but can also alter the structure and composition of bacterial communities associated with citrus leaves (6), roots (7), and rhizospheres (8). In our investigation conducted to identify fungal species in orange juice from HLB-symptomatic ("Ca.…”
mentioning
confidence: 99%